Interlingual and Interlingual Communication in Brunei Darussalam: Some Factors Governing Code Choice - Martin, Peter W. (Journal of Modern Languages, 2017)
This study examines a number of aspects of language use in Negara Brunei Darussalam. Its main emphasis is on the use of Malay in intergroup and intragroup communication and on which particular varieties of the language are selected for various purposes. It is also concerned with the function of the minority languages in the country. A number of factors affecting code selection are considered.